OJ - 51 - ECOWAS (ECOWAS, 2007)
Thirty Second Session of the Authority of Heads of State and Government, Abuja, Nigeria. 15th June 2007. Fifty-Eighth Ordinary Session of the Council Of Ministers, Ouagadougou, Burkina Faso. A - 5 June 2007.
ECOWAS
Keywords: International Economic Integration; Periodicals; Gazettes; Economic Community of West African States; Africa, West; Economic Integration